Gambaran Penerapan Pendokumentasian Asuhan Keperawatan Berbasis Elektronik - Nurain Ino; Nanang R. Paramata; Moh. Nisyar Sy. Abd. Azis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the implementation of electronic nursing care documentation in the inpatient wards of Toto Kabila Regional Hospital. A quantitative, non-experimental, descriptive approach was used, with a sample of 142 nurses. The results showed that the majority of respondents rated the implementation of electronic nursing care documentation as good (108 respondents; 76.1%), while a minority rated it as fair (34 respondents; 23.9%). The best implementation was in the Urology Surgery Room with the highest mean score of 1.91, while the lowest was in the Isolation Room with a mean score of 1.59. In conclusion, the majority of nurses (76.1%) rated the implementation of electronic nursing care documentation at Toto Kabila Regional Hospital as good. In conclusion, although some (23.9%) encountered technical and training challenges, all respondents (100%) stated that the system was effective and beneficial, particularly for rapid data access, efficiency, team coordination, and accuracy, thus supporting improved nursing care quality. Keywords: HOT FIT, Electronic Nursing Care Documentation, Inpatient Nurses